The effect of socioeconomic status on ambulance requests in Mashhad, Iran - Dadashi, Ali; Kalani, Mohamad Reza; Vafaeinejad, Reza; Eslami, Saeed (European Journal for Biomedical Informatics, 2019)
Objectives: Emergency medical events are not randomly distributed over a certain area. Many hidden patterns may influence this distribution due to several socioeconomic, demographic, and geospatial factors. Identifying these patterns will help health policy makers have a better planning for emergency medical services (EMS) in finding high-risk places, and people at high risk. Methods: Mashhad city EMS calls records have been analyzed retrospectively. The data came from a city wide registry including 154528 calls to EMS from March 21, 2013 to March 20, 2014. To recognize the location of the requests all the recorded addresses were mapped into a single number representing the municipality district of the call. Pearson correlation coefficient is used to represent the association between ambulance calls and socioeconomic factors (e.g. income level, house ownership). Results: The average of age of the patients is 42.43 years (S.D=21.7) with 50.5% male, 40.7% female and 8.8% of the sex are not registered. 64% of the calls are medical related and the remaining 36% are trauma related requests. Although the regions with lower socioeconomic status are more vulnerable, they request ambulances less frequently than the regions with higher socioeconomic status. The ambulance requests are more frequent in regions with higher education (university studies) than the regions with lower education. In addition, there is a relationship between the economic status of people and their ambulance requests that regions with higher economic status request ambulances more frequently. Conclusion: Results of the study shows that there is a relationship between the socioeconomic status of people and their calls to EMS that can help policy makers in finding people in potentially high risk locations and provide services to reduce mortality and morbidity.
Keywords: urgentní zdravotnické služby; Registries; Telephone; registrace; socioekonomické faktory; Írán; Iran; telefon; Emergency Medical Services; Socioeconomic Factors